The Urgency of Islamic Legal Education: Shaping the Character of Individuals with Ethics and Justice - Samsuddin, Samsuddin (ETDC: Indonesian Journal of Research and Educational Review, 2023)
Islamic law education plays an important role in the process of developing public law awareness. The research problem pertains to the definition of Islamic law and the pressing need for Islamic law education. The research aims to investigate how Islamic law shapes the character and justice of individuals. The research methodology employs the literature review method. We conducted a comprehensive analysis of pertinent literature, encompassing Islamic law theory. The results of the research played an important role in the learning process and the development of public law awareness. Through Islamic law education, we can create a learning environment that prioritizes honesty, morality, and independence and creates people who contribute to society. Through proper education, people can not only understand the law but also internalize the moral and ethical values contained in Islamic law.